Increase Activity, Critical Thinking Skills and Student Collaboration Using the PERMATA Model and Wordwall Media in Elementary Schools - Noppy Ridhani; Ahmad Suriansyah; Ratna Purwanti (Indonesian Journal of Primary Education, 2024)
This research raises the problem of low critical thinking skills and student cooperation in science and science lessons in elementary schools due to learning that is not focused on students and the use of learning models is still lacking. This problem can be overcome by implementing a combination of learning models, namely the PERMATA model (Problem BasEd LeaRning, SAVI (SoMatic, Auditory, VisuAlization, dan Intellectually), dan Two Stay Two StrAy) and Wordwall Media. The aim of this research is to describe the improvements that have occurred in activities, critical thinking and collaboration skills, as well as the learning outcomes obtained by students. This research applies PTK research or classroom action research with fourth grade students at SDN Terantang 2 who act as research subjects. The method used is a qualitative and quantitative approach. The results of the research concluded that during the 4 meetings there was an increase in teacher activity with very good criteria, student learning activity increased from less active to very active, students' critical thinking and collaboration skills increased from less skilled to very skilled, and student learning outcomes increased. Based on the findings, it can be concluded that the use of the PERMATA model and Wordwall media is effective in increasing activity, critical thinking and collaboration skills, as well as student learning outcomes. The results of this research are recommended as reference material for similar research in efforts to improve the quality of learning in elementary schools.